2006
DOI: 10.1007/s10803-006-0286-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Circumscribed Interests on the Social Behaviors of Children with Autism Spectrum Disorders

Abstract: This study compared the effects of circumscribed interests (CI) to less preferred (LP) tangible stimuli on the social behaviors of three children with autism spectrum disorders (ASD). Based on single subject design methodology, the CI experimental sessions resulted in longer durations of target-child initiated social interactions in comparison to LP sessions. In addition, latency of participant's initial social bids to peers was decreased when CI were present. The results suggest that embedding CI into dyadic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
127
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(140 citation statements)
references
References 34 publications
9
127
2
2
Order By: Relevance
“…Several investigators have observed that interactions with robots motivate prosocial behaviors and learning in children with ASD (Dautenhahn, 2003;Diehl et al, 2012;Kim et al, 2013). Moreover, it has been noted that the prosocial behaviors gained during interactions with therapeutic robots transfer to real-life interactions with peers and adults (Boyd, Conroy, Mancil, Nakao, & Alter, 2007;Diehl et al, 2012). Perhaps, by drawing on their interest in robots, children with ASD can be motivated and encouraged to collaborate with their typically-developing peers on robot development projects (Kaboski et al, 2015;Wainer, Ferrari, Dautenhahn, & Robins, 2010).…”
Section: Capitalizing On Technology/robotics Interests Among Studentsmentioning
confidence: 99%
“…Several investigators have observed that interactions with robots motivate prosocial behaviors and learning in children with ASD (Dautenhahn, 2003;Diehl et al, 2012;Kim et al, 2013). Moreover, it has been noted that the prosocial behaviors gained during interactions with therapeutic robots transfer to real-life interactions with peers and adults (Boyd, Conroy, Mancil, Nakao, & Alter, 2007;Diehl et al, 2012). Perhaps, by drawing on their interest in robots, children with ASD can be motivated and encouraged to collaborate with their typically-developing peers on robot development projects (Kaboski et al, 2015;Wainer, Ferrari, Dautenhahn, & Robins, 2010).…”
Section: Capitalizing On Technology/robotics Interests Among Studentsmentioning
confidence: 99%
“…In autism, restricted, repetitive behaviors are often grouped into two basic categories: lower and higher order interests [11]. Lower order interests are characterized by repetition of movement, and include motor stereotypies, self-injurious behaviors, object fixations, and repetitive manipulations of objects.…”
Section: Background 21 Autism Spectrum Disordementioning
confidence: 99%
“…Most behavioral interventions that use SIs can be divided into two approaches: consequent-based and antecedentbased [11]. Consequent-based approaches leverage the SI as a reward that can be enjoyed after completing a task or after a period of good behavior.…”
Section: Background 21 Autism Spectrum Disordementioning
confidence: 99%
See 2 more Smart Citations